Um Controlador de Tráfego Ferroviário Adaptável Simulado com Máquinas de Estado Finitas - BRAGA, Reginaldo Isaias (2004)
This thesis deals with implementation of a railway control interlocking simulator whose functional requirements can be adaptive, that is, modified, complemented or same redefined, through an approach based on Finite State Machines. Depending on its requirements, a controller of rail traffic can assume simple or critics characteristics in terms of safety or fault tolerance. The modeling based on the Finite State Machine approach provides the conditions for the adaptability of some functional requirements. This characteristic is emphasized better when we used automated tools of definition of state machines, which allow the easy integration with the remaining of the software application. A detailed discussion about safety's considerations in design of mission and safety critical systems is presented. Emphasis is given in the subjects related to the safety software. A methodology and tool (SpecTRM-RL) that implements it, derived of recent researches in safety software, is shown. These considerations are fundamental in the design and requirements analysis in railway s interlocking control systems. These kinds of systems can be classified as mission and safety critical and they are progressively migrating for relay based controllers to microprocessor-based controllers where in the whole or partly safety's requirements are implemented by software. Fault tolerance techniques either in software or hardware are fundamental in the context of this work. A selection of the most usual in systems that demand high reliability was detailed with the goal of emphasizing its potential application in the case study of a railway control-interlocking simulator.